1995
DOI: 10.1016/0550-3213(94)00525-j
|View full text |Cite
|
Sign up to set email alerts
|

The tau weak-magnetic dipole moment

Abstract: We calculate the prediction for the anomalous weak-magnetic form factor of the tau lepton at q 2 = M 2 Z within the Standard Model. With all particles on-shell, this is a electroweak gauge invariant quantity. Its value is a w τ (M 2 Z ) = − (2.10 + 0.61 i) × 10 −6 . We show that the transverse and normal components of the single-tau polarization of tau pairs produced at e + e − unpolarized collisions are sensitive to the real and absorptive parts of the anomalous weak-magnetic dipole moment of the tau. The sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…Re µ τ , Im µ τ , Re d τ and Im d τ . Radiative corrections in the SM provide nonzero predictions for µ τ and d τ [1,2] which are below the present experimental sensitivity. This opens the possibility to look for deviations from the SM.…”
Section: Introductionmentioning
confidence: 99%
“…Re µ τ , Im µ τ , Re d τ and Im d τ . Radiative corrections in the SM provide nonzero predictions for µ τ and d τ [1,2] which are below the present experimental sensitivity. This opens the possibility to look for deviations from the SM.…”
Section: Introductionmentioning
confidence: 99%
“…2. As we said before, a Z τ | EW is given in [7] and a detailed computation of a Z τ | 2HD can be found in [8]. We will not repeat these results here, but we want to stress that we have checked the analytical formulae and the numerical results presented in [8].…”
Section: The τ Leptonmentioning
confidence: 92%
“…and was calculated by Bernabéu et al [7]. They showed that a Z τ in the SM is dominated by W − ν diagrams.…”
Section: The τ Leptonmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the notation of references [11] and [14], we now show how to measure the EDM using low energy CP -odd observables. At low energies and in the hypothesis stated above, the EDM gives contributions to leading order in the Normal-Transverse and Normal-Longitudinal correlation terms of the…”
Section: Low Energy Observablesmentioning
confidence: 99%